Contracting for services in state and local government agencies : best practices for public procurement - Curry, William Sims (London ; New York : Routledge, 2023)
"This book provides state-of-the-art tools for best practice in the procurement of services at state and local levels, throughout the procurement cycle. Including lively case studies and research conducted with state and local agencies across the United States, this award-winning book provides management advice and tips on compliance to reduce costs, select the best-qualified contractors, manage contractors' performance, and prevent corruption and waste. Utilizing the results of new research across states, cities, counties, and institutes of higher learning, this third edition offers 18 all-new best-practice documents as well as updated methodologies and templates including but not limited to: a full-length and short-form Request for Proposal (RFP), a full-length and short-form Pro Forma Contract (PFC), letter contracts, a sample estimate at completion, a contract amendment template, and a form for evaluation of proposals. Special consideration is given to obtaining services and products during states of emergency. Several additional resources for instructors and professionals are available online, including templates and PowerPoint slides"--
Research Conducted on Best Practices for Public Procurement -- Introduction, Advance Procurement Planning, and the Procurement Cycle -- Socioeconomic and Competitive Procurement -- Solicitation Documents : Information for Prospective Contractors -- Management of Pre-Proposal Communications and Evaluation of Proposals -- Protests -- Contract Negotiations, Ethics, and Conflicts of Interest -- Contract Document -- Contract Terms and Conditions -- Short Form Contracts, Short Form RFPs, Emergencies, and Letter Contracts -- Contract Review, Execution, and Audit -- Contract Administration and Closeout.
OCLC-licensed vendor bibliographic record.
Keywords: Contracting out -- United States -- States; County services -- Contracting out -- United States; Municipal services -- Contracting out -- United States; Public contracts -- United States -- States; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Government / General; BUSINESS & ECONOMICS / Purchasing & Buying